INDICATIONS FOR THE TREATMENT OF GASTROINTESTINAL ULCERS WITH ANTIBACTERIAL DRUGS - Bazarova Albina Muhammadjonovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the clinical indications for the use of antibacterial therapy in the management of gastrointestinal (GI) ulcers. Particular emphasis is placed on Helicobacter pylori (H. pylori)-associated peptic ulcers, non-H. pylori-related infections, and cases involving secondary bacterial complications. The paper outlines diagnostic criteria, pharmacological strategies, and current international guidelines for implementing antibacterial treatment. The importance of antibiotic stewardship and resistance prevention is also discussed.